2006
DOI: 10.1080/14622200601042513
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative analysis of an Internet discussion forum for recent ex-smokers

Abstract: We conducted a qualitative analysis of all messages posted in April 2005 on an online discussion forum aimed at recent ex-smokers, on the smoking cessation Web site Stop-tabac.ch. We analyzed only the forum aimed at recent ex-smokers because it was far more active than forums aimed at current smokers. Participants were 97 people who posted a total of 1,033 messages (mean= 10.6 messages per participant). Most (76%) participants were women, the median age was 40 years, and participants had quit smoking for a med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 19 publications
3
60
0
1
Order By: Relevance
“…Prominent were sentiments of encouragement and specific suggestions as to what worked for each member, a finding that is common in analyses of other online support groups [15,17]. Beyond the informational and support content, two other primary themes emerged from the analysis of the AHC support group content.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Prominent were sentiments of encouragement and specific suggestions as to what worked for each member, a finding that is common in analyses of other online support groups [15,17]. Beyond the informational and support content, two other primary themes emerged from the analysis of the AHC support group content.…”
Section: Discussionmentioning
confidence: 92%
“…To-date there has been little published guidance on how to initiate online group discussions, create long-lasting and self-sustaining communities, or effectively and efficiently empower participation while simultaneously ensuring the highest quality content. Burri et al [17] conducted a qualitative analysis of the content of an online support group for smokers. They concluded that the support group was mainly used as a source of support and encouragement during the initial phases of quitting cigarettes.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison with static websites suggests that an interactive user interface boosts the treatment effect, although it is unclear what form of interaction is required to confer this benefit. While it has been speculated that chat forums could aid smoking cessation through the provision of additional social support [53,54], it appears that completely automated interventions may be more effective. There was no evidence that increasing treatment complexity improved cessation rates, but this could reflect a ceiling effect, as all reviewed interventions were already highly complex.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis was not restricted to specific countries because we were interested in representing views across different regulatory contexts. Additionally, a person who writes a comment on the forum (a 'poster') does not have to be living in a particular country to join, or access, a forum and will not always provide a country of residence (Burri et al, 2006).…”
Section: Data Collectionmentioning
confidence: 99%
“…Accordingly, online forums offer a new medium to explore public discussions about smoking cessation and harm reduction (e.g. Burri, Baujard, & Etter, 2006). We analysed 13 online forums discussing vaping during pregnancy, with an interest in how forum posters debated the safety of e-cigarette use during pregnancy.…”
Section: Introductionmentioning
confidence: 99%